Comparison of molecular methods for Bartonella henselae detection in blood donors. - Marina Rovani Drummond; Luciene Silva Dos Santos; Amanda Roberta de Almeida; Karina de Almeida Lins; Maria Lourdes Barjas-Castro; Pedro Paulo Vissotto de Paiva Diniz; Paulo Eduardo Neves Ferreira Velho (PLoS Neglected Tropical Diseases, 2023)
The Bartonella genus consists of neglected pathogens associated with potentially transfusional-transmitted and fatal human diseases. We aimed to evaluate Bartonella sp. prevalence in 500 blood donors and compare the results with the data already published about these samples. We used molecular diagnostic methods to detect Bartonella sp.-DNA from blood and liquid culture samples: (A) conventional PCR for two gene regions, the ITS targeting the genus Bartonella and the specific gltA Bartonella henselae; (B) nested PCR for the ftsZ gene and (C) qualitative real-time PCR for the gltA gene, both B. henselae specific. We obtained 30/500 (6%) DNA detections from the blood samples; 77/500 (15.4%) DNA detections from liquid culture samples and five (1%) samples had DNA detection from both. In total, we detected B. henselae DNA from 102/500 (20.4%) donors. The samples used in this study had already been submitted for Bartonella sp.-DNA detection using only a conventional PCR in liquid culture. Sixteen samples (3.2%) were positive previously, and from these 16 samples, 13 were negative in the new investigation. We concluded that the use of liquid culture combined with different molecular tests increases the possibility of detecting Bartonella sp.-DNA, but the tests do not avoid false-negative results. More than a fifth of blood donors had at least one PCR that detected Bartonella sp.-DNA among the eight molecular reactions performed now (four reactions in whole blood and four in liquid culture). Seven percent had B. henselae-DNA detection for two or more distinct regions. Considering the results obtained previously, the DNA of Bartonella spp. was detected or the agent isolated in 23% of analyzed blood donors. The results establish that the low bacteremia and the fastidious characteristics of the bacterium are challenges to laboratory diagnosis and can make it difficult to confirm the infection in patients with bartonelloses.